Women Empowerment and socioeconomic inequality in immunization coverage: a case study of Zambia - Mojapelo, Thato (Department of Public Health and Family Medicine, 2021)
Basic immunisation coverage for children between 12-23 months in Zambia was 68% in 2013. Nevertheless, a substantial number of child deaths persist as a result of preventable disease. This study assesses the relationship between women empowerment and immunisation coverage in Zambia. It also investigates socio-economic inequality in full, partial, and immunisation intensity. Thus, the findings will support improved immunisation coverage, especially for those who are the poorest in Zambia. The study uses the 2013-14 Zambia Demographic and Health Surveys (ZDHS), which are nationally representative household surveys [12]. This dataset incorporates information regarding children from 0 to 59 months and for men and women aged 15- 49 years old. The two main study variables are women empowerment and immunisation. Immunisation was divided into three categories namely, full, partial and no immunisation. Concentration indices are used to assess inequality in full, partial and no immunisation coverage as well as in the intensity of immunisation coverage. Briefly, a positive concentration index means that immunisation coverage is pro-rich as richer children are more likely to be immunised. A negative index indicates the opposite. The main finding of this study was that socioeconomic status has a significant impact on the immunisation coverage of a child. For children who were fully immunised, immunisation was found to be pro-rich (concentration index = 0.046). The distribution of partially immunised children (concentration index = -0.114) and not immunised children (concentration index = -0.138) is pro-poor. This confirmed that poorer women were more likely to have a partially immunised/not immunised children compared to a child whose mother is richer. Immunisation intensity had a pro-rich outcome (concentration index = 0.153). In addition, the study confirmed the importance of household decision making as a determinant of a child's likelihood of being fully immunised (p-value< 0.01). This study has shown that close attention to factors such as women empowerment and a mother's education can support improved immunisation coverage, especially for those who are the poorest in Zambia. This paper further highlighted the importance of socio-economic status as it impacts on immunisation coverage.